Parasitoid-host interaction: sensory structures involved in the parasitism behavior of Bracon vulgaris (Hymenoptera: Braconidae) - Alves, Thiago J. S.; Wanderley-Teixeira, Valeria; Teixeira, Alvaro A. C.; Silva-Torres, Christian S. A.; Malaquias, Jose B.; Pereira, Bruno F. [UNESP]; Caetano, Flavio H. [UNESP]; Cunha, Franklin M. da (Brill Academic Publishers, 2014)
Parasitoids have evolved mechanisms to evade their hosts' defenses. Bracon vulgaris (Ashmead) is a larval ectoparasitoid responsible for natural reduction of Anthonomus grandis (Boheman) and Pectinophora gossypiella (Saunders), which are considered the main cotton pests in the cotton agroecosystem in northeastern Brazil. This study aimed to analyze the sensory structures (antennae and ovipositor) involved in the parasitism behavior of B. vulgaris, and to describe and evaluate associations between composition, morphology, and functions of these structures in the parasitoid-host interaction. Results showed that the B. vulgaris ovipositor is a multifunctional structure of 2.7 0.3 mm in length composed of 3 valves. Valves 1 and 2 are elongated, rigid, and act jointly to pierce the host's cuticle, to inject the poison glands secretion, and to deposit eggs. Valve 3 covers the other valves, giving them protection. Valve 3 also presents annulations in all its extension, which gives flexibility to the ovipositor, and trichoid sensilla that possibly capture vibrations from the host's feeding and locomotion, thereby aiding the parasite in the host selection. The presence of cuticular microtrichia was possibly responsible for the cleaning of the ovipositor, keeping it functional between the various insertions that occur during the parasitism behavior. The parasitoid's antennae are filliform-like, measure about 2 mm, and are composed of four types of sensilla (trichoids, basiconical, coeloconical, and placodes) that act as olfactory and gustatory receptors and/or express tactile, thermo,- and hygroreception functions. The integrated action of these sensory components corroborates the successful parasitism behavior of the parasitoid B. vulgaris.
Keywords: Ectoparasitoid; host selection; parasitism behavior; scanning electron microscopy; sensory organs; successful parasitism